ANALISIS KONTRIBUSI EKONOMI KERAJINAN ANYAMAN PURUN TERHADAP PENDAPATAN MASYARAKAT - Rizki, Gusti Eviyani; Hafizianor, Hafizianor; Rahmadi, Adi (Lambung Mangkurat University-Indonesia, 2025)
South Kalimantan has quite potential purun plant raw materials, most of the South Kalimantan area consists of swamps that are always inundated throughout the year and have a peat soil structure that is acidic (pH-7) which is a place for purun plants to grow. This research will be conducted in Palam Village, Cempaka District, Banjarbaru City. The method used in this study is based on interviews related to the main and secondary income of purun craftsmen, total income and its contribution to community income. While secondary data collection includes data on the general conditions of the research location; socio-economic data of the community, both in the form of population, education level, livelihood and amount of income. From the results of the study, it was stated that purun woven crafts made a significant contribution to increasing community income in Palam Village. With an economic contribution of 21.11% to the average main income of residents, this craft has become an important source of income that helps improve local economic welfare. Purun woven products, in addition to being aesthetically valuable crafts, also function as environmentally friendly alternatives for various needs, so that demand continues to increase both in the local and outside markets. This increase in income shows the great potential of purun crafts in strengthening the local economy.